Pengaruh Service Quality Dan Promotion Terhadap Intens To Repurchase Jasa Service Motor Dengan Customer Satisfaction Sebagai Intervening Variable (Studi Pada Bengkel Motor Ahass Cabang UMS) - Pratiwi, Anggrahini Panca; , Sri Murwanti, SE. M.M (2017)
This study aims to determine the effect of service quality, and promotion of the intense to repurchase at a motor service services mediated by customer satisfaction. Based on the results of the study are expected to provide input to improve or expand a business in the future. The study was conducted to 100 respondents is the consumer who is trading at the bike shop AHASS UMS branch. The sampling technique in this study using a non-probability sampling method used was accidental sampling. Data analysis tool used is simple regression in SPSS. Results of analysis of the data shows the validity and reliability showed that the concept of variable service quality, promotion, customer satisfaction and intense to repurchase fit for use as a measuring tool. The research model has a good fit, and all the research hypothesis can be proven true that partially or simultaneously variable service quality and promotion mediated by customer satisfaction and significant positive effect on intense to repurchase.